ORGANIZATIONAL AND SOCIO-PSYCHOLOGICAL ASPECTS OF MANAGERIAL COMPETENCE IN THE ACTIVITY OF A LEADER (American Journal of Business Management, Economics and Banking, 2024)
The managerial decision depends on many factors: on the state of affairs in the controlled area, on the state of the labor collective, on staffing, etc. In addition, management makes special demands on the personal qualities of a leader, on his mental abilities, on his ability to predict and analyse emerging managerial situations.